2014
DOI: 10.4196/kjpp.2014.18.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Regular Exercise Training Increases the Number of Endothelial Progenitor Cells and Decreases Homocysteine Levels in Healthy Peripheral Blood

Abstract: Endothelial progenitor cells (EPCs) are known to play an important role in the repair of damaged blood vessels. We used an endothelial progenitor cell colony-forming assay (EPC-CFA) to determine whether EPC numbers could be increased in healthy individuals through regular exercise training. The number of functional EPCs obtained from human peripheral blood-derived AC133 stem cells was measured after a 28-day regular exercise training program. The number of total endothelial progenitor cell colony-forming units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
11
1
1
Order By: Relevance
“…Some researchers highlighted an exercise-induced-fall in tHcy after training: the investigations of Randeva et al [12] and Choi et al [13] included aerobic modalities and Vincent et al [27] and [30] performed resistance programs [12,13,27,30]. Thus, we did not find the common point among these results, due to the differences in the type of exercise, training duration and sample studied.…”
Section: Effect Of Chronic Exercise On Thcy Concentrationscontrasting
confidence: 52%
See 1 more Smart Citation
“…Some researchers highlighted an exercise-induced-fall in tHcy after training: the investigations of Randeva et al [12] and Choi et al [13] included aerobic modalities and Vincent et al [27] and [30] performed resistance programs [12,13,27,30]. Thus, we did not find the common point among these results, due to the differences in the type of exercise, training duration and sample studied.…”
Section: Effect Of Chronic Exercise On Thcy Concentrationscontrasting
confidence: 52%
“…But there is also a huge variety in the methodology applied among all the studies, hence, there is difficulty to reach an agreement [5]. Some researchers have demonstrated reduced tHcy concentrations after a training period [12,13]; others have related high PA levels and cardiorespiratory fitness with lower homocysteine concentrations [14,15]. In contrast, some studies have shown higher tHcy concentrations after acute exercise, training period or after a specific sport competition [16][17][18].…”
Section: Introductionmentioning
confidence: 87%
“…Individuals that exercised regularly for 28 days exhibited reduced plasma homocysteine levels and increased endothelial progenitor cells in peripheral blood, factors that protect against vascular damage and cognitive impairment [237]. Experimental studies in diabetic rats have shown that treadmill exercise maintains claudin-5 expression at the BBB compared to rats not receiving exercise [238].…”
Section: Vasculoprotective Approachesmentioning
confidence: 99%
“…It is important to remember that this effect is different from the effects found in chronic exercise. Some researchers reported an exercise-induced reduction in tHcy after training (Randeva et al 2002;Vincent et al 2003Vincent et al , 2006Choi et al 2014), while other studies showed that training did not contribute to decreased tHcy concentrations (Boreham et al 2005). Interestingly, Okura et al (2006) found different responses depending on the baseline tHcy status; for example, increased tHcy levels were observed after training in subjects with normal tHcy concentrations at baseline, while the opposite effect (i.e.…”
Section: Discussionmentioning
confidence: 99%